2010
DOI: 10.1128/jcm.00734-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tcdB Real-Time PCR in a Three-Step Diagnostic Algorithm for Detection of Toxigenic Clostridium difficile

Abstract: Clostridium difficile is the most common infectious cause of diarrhea in hospitalized patients. The optimal approach for the detection of toxigenic C. difficile remains controversial because no single test is sensitive, specific, and affordable. We have developed a real-time PCR method (direct stool PCR [DPCR]) to detect the tcdB gene encoding toxin B directly from stool specimens and have combined it with enzyme immunoassays (EIAs) in a three-step protocol. DPCR was performed on 699 specimens that were positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 59 publications
5
69
2
1
Order By: Relevance
“…Very occasionally, a patient with ileus and complicated disease will have a formed stool ( 3 ), in which case the laboratory should be made aware of this special clinical situation. Rectal swabs can be used for PCR 26. In patients with IBD, ongoing immunosuppression medications can be maintained in patients with CDI.…”
Section: Microbiology and Diagnosismentioning
confidence: 99%
“…Very occasionally, a patient with ileus and complicated disease will have a formed stool ( 3 ), in which case the laboratory should be made aware of this special clinical situation. Rectal swabs can be used for PCR 26. In patients with IBD, ongoing immunosuppression medications can be maintained in patients with CDI.…”
Section: Microbiology and Diagnosismentioning
confidence: 99%
“…1 However, this approach often requires several days to complete, and neither assay is commonly available in clinical laboratories. The recent comprehensive study of C. difficile detection methods, 2 which reported the sensitivity of a commonly used GDH assay as 87.6% when compared with toxigenic culture, is consistent with concerns of falsely GDH-negative samples raised by the report of Larson et al 48 NovakWeekley et al 34 reported that initial GDH screening failed to identify approximately 15% of samples containing toxigenic C. difficile isolates. In addition, the mean sensitivity of membrane-type GDH assays in the ESCMID survey was only 60% when compared with toxigenic culture, 3 suggesting that GDH screening may not be as highly sensitive as previously assumed.…”
Section: Gdh Assaysmentioning
confidence: 62%
“…All four patients had subsequent stool samples that were positive by both PCR and toxigenic culture, and a review of the patients' medical records revealed that three of four patients already had been treated for CDI. 48 Thus, retesting of GDH-negative samples by PCR lowered the sensitivity of the GDH algorithm from 97.1% to 83.8%, and the negative predictive value also decreased from 99.7% to 97.9%.…”
Section: Pcr Assaysmentioning
confidence: 95%
See 2 more Smart Citations